Spam detection by using machine learning based binary classifier - Mohd Fadzil Abdul Kadir; Ahmad Faisal Amri Abidin; Mohamad Afendee Mohamed; Nazirah Abdul Hamid (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Because of its ease of use and speed compared to other communication applications, email is the most commonly used communication application worldwide. However, a major drawback is its inability to detect whether mail content is either spam or ham. There is currently an increasing number of cases of stealing personal information or phishing activities via email. This project will discuss how machine learning can help in spam detection. Machine learning is an artificial intelligence application that provides the ability to automatically learn and improve data without being explicitly programmed. A binary classifier will be used to classify the text into two different categories: spam and ham. This research shows the machine learning algorithm in the Azure-based platform predicts the score more accurately compared to the machine learning algorithm in visual studio, hybrid analysis and JoeSandbox cloud.